Quasi-normally off AlGaN/GaN high-electron-mobility transistors with p-type CuOx gate synthesized through magnetron reactive sputtering. (February 2023) - Lu, Honghao; Wen, Kangyao; Du, Fangzhou; Tang, Chuying; Cheng, Wei-Chih; Wei, Bowen; Li, Honglin; Wang, Qing; Yu, Hongyu
Abstract: In this study, magnetron reactive sputtering using a copper oxide target was performed to obtain a series of high-quality CuOx films with high hole concentration. The results of X-ray photoelectron spectroscopy and Hall measurements revealed that the hole concentration exhibited a negative correlation to the Cu + to Cu 2+ ratio in the p-type CuOx film. This phenomenon indicated that the hole concentration can be modulated by adjusting film deposition conditions. Considering the high hole concentration and fine surface quality, these CuOx films were used as p-type gates without gate etching and positively shifted the threshold voltage ( V th ) of AlGaN/GaN high-electron-mobility transistors (HEMTs). This study is the first to achieve quasi-normally off GaN HEMTs using CuOx gates, in which V th positively shifted approximately 2.5 V and reached 0.5 V. Because of the excellent surface quality of the CuOx gate, the off-state current and gate leakage current of GaN HEMTs improved considerably. This study verified that CuOx is a promising gate candidate for fabricating low-cost, normally off AlGaN/GaN HEMTs. Graphical abstract: Image 1 Highlights: P-type CuOx gates were obtained through magnetron reactive sputtering of a copper oxide target. For the first time, a quasi-normally off AlGaN/GaN HEMT with a CuOx gate was achieved. The Cu + to Cu 2+ ratio in CuOx films was inversely proportional to hole concentration. Adjustment of Cu + :Cu 2+ in CuOx gates allows the fabrication of AlGaN/GaN HEMTs with different threshold voltages.